Left-handed : getting a grip on handedness - Birmingham, Maria (Owlkids Books, 2026)
"Most of us define ourselves as lefties or righties based on the hand we use for writing. But what makes people prefer one hand over the other? And what if handedness doesn't tell the whole story? Do we also favor one eye, ear, or foot? What about people who use different hands for different activities? That's where this book comes in. It examines all things lefty--from handedness in our ancient ancestors to lefty myths to current theories about the roles of genetics, environment, and brain structure. It also tackles questions such as: Why and when does someone become a lefty? Are humans the only left-handed animals? And what is it like to live a left-handed life in a right-handed world? By gently disrupting traditional lefty/righty thinking, Left-handed celebrates the differences that make each of us unique."--